Program Kreativitas Mahasiswa Pembuatan Hand Grip Modern Untuk Bandminton Tahun 2021 - Achamd Zakaria; Restian Gigih Sejati; Slamet Riyadi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2021)
The aim of this research is to create a racket grip modification product to improve grip techniques in badminton. The research approach used is development research. The results of the research obtained a value for aspect 1 regarding "while participating in badminton using modified racket grip media, how do you feel?" 84% of respondents felt happy. Aspect 2. "Is the modification used as a towel holder with adhesive, what do you feel?" 79% of respondents found it easier to learn. The use of badminton racket grip products has a positive impact on students learning racket grip techniques. STKIP Darussalam created this program to increase knowledge, especially for STKIP Darussalam students, about how important handgrips are in providing comfort to badminton players. This program was able to be implemented well thanks to the cooperation of PJKR students. This program was successfully implemented well as seen from the results of the questionnaire given.